Pengaruh Profitabilitas, Solvabilitas, Opini Audit Dan Ukuran Perusahaan Terhadap Audit Delay Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Nurul Iftina Azalia (Asosiasi Dosen Akuntansi Indonesia, 2021)
The problem in this research is based on the announcement issued by the Indonesia Stock Exchange on April 11, 2018 regarding the Submission of Audited Financial Statements ending December 31, 2017 that there are 70 listed companies that have not submitted their financial statements and one of them comes from the mining sector. This study aims to analyze whether profitability, solvency, audit opinion and company size have an effect on audit delay in mining companies listed on the IDX in 2017-2019. By using purposive sampling method from 51 populations, there are 27 samples that are ready to be studied. So the total sample in this study is 81 (27 x 3). Furthermore, the data will be analyzed using descriptive statistical analysis methods and logistic regression analysis. The results of this study indicate that partially profitability, solvency, audit opinion and firm size have no significant effect on audit delay. while simultaneously profitability, solvency audit opinion and firm size have a significant effect on audit delay. Companies should increase awareness of the importance of submitting financial reports in a timely manner in order to avoid sanctions imposed by the Indonesia Stock Exchange